INFLUENCE OF INSTITUTIONAL OWNERSHIP, OWNERSHIP PUBLIC, CAPTAIN SIZE, LIQUIDITY AGAINST ACCURACY FINANCIAL REPORTING TIMES IN PROPERTY COMPANIES AND REAL ESTATE WHICH LISTED ON THE EXCHANGE EFFECT INDONESIA - Fensiski, Jenna Tiffanny; Evelyn; Zain, Jenny; Syahputra, Oky (Jurnal Ipteks Terapan, 2024)
These property and real estate shares are owned by the public. Purposeful testing Influence Ownership Institutional, Ownership Public, Size HOOD, Liquidity to Accuracy Time Reporting Finance On Company Property and Real Estate listed on the Indonesian Stock Exchange. Approachable quantitative with use regression logistics. The research nature causal. Population amount 65 Company Property And Real Estate Which registered in Exchange Effect Indonesia period 2018-2021. Sample amount 76. The model regression logistics. The result is Ownership Institutional, size KAP is influential to Accuracy Time Reporting Finance On Company Property And Real Estate Which registered in Exchange Effect Indonesia. Ownership Public, liquidity No influence the timeliness of financial reporting in companies Property and Real Estate listed on the Indonesian Stock Exchange. Ownership Institutional, Public Ownership, KAP Size, Liquidity have an influence on Timeliness of Financial Reporting in Property and Real Estate Companies Which registered in Exchange Effect Indonesia.